2010
DOI: 10.5198/jtlu.v3i3.98
|View full text |Cite
|
Sign up to set email alerts
|

Residential location, travel, and energy use in the Hangzhou Metropolitan Area

Abstract: Abstract:is paper presents the results of a study examining the in uence of residential location on travel behavior in the Hangzhou Metropolitan Area, China. e location of the dwelling relative to the center hierarchy of the metropolitan area is found to exert a considerable in uence on the travel behavior of the respondents. On average, living close to the center of Hangzhou contributes to less overall travel, a higher proportion of trips by bicycle and on foot, and lower consumption of energy for transport.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 17 publications
4
37
0
1
Order By: Relevance
“…Many of the findings in this paper support previous studies from other cities in the global South, namely that there are significant differences in individuals travel behavior between districts within the same city; individuals in peripheral and sparsely settled areas travel longer distances, use private motor vehicles more often (for most or all trip purposes), cars in particular, and travel more frequently (Srinivasan and Rogers, 2005;Tanimowo, 2006;Naess, 2009;Wang et al, 2011;Shirgaokar, 2016). Comparisons between districts with different characteristics within the same urban area are useful as it enhances our understanding of how planning policies play out and takes on meaning within the city system.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Many of the findings in this paper support previous studies from other cities in the global South, namely that there are significant differences in individuals travel behavior between districts within the same city; individuals in peripheral and sparsely settled areas travel longer distances, use private motor vehicles more often (for most or all trip purposes), cars in particular, and travel more frequently (Srinivasan and Rogers, 2005;Tanimowo, 2006;Naess, 2009;Wang et al, 2011;Shirgaokar, 2016). Comparisons between districts with different characteristics within the same urban area are useful as it enhances our understanding of how planning policies play out and takes on meaning within the city system.…”
Section: Discussionsupporting
confidence: 79%
“…Pan et al (2009), studying the influence of urban form on travel behavior in four Shangahi neighborhoods, found that residents of pedestrian/cyclist-friendly neighborhoods traveled shorter distances compared to residents in other neighborhood types. Likewise, Naess (2009), studying the influence of residential location on travelling behavior in Hangzhou Metro Area, found that, on average, people living close to the CBD used less energy for transport; they travelled less in total and made a greater share of their journeys by bike or on foot compared to people further away from the downtown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This applies not only to the influence of residential location on traveling distance by car, but also on total weekly traveling distances, travel by non-motorized modes, and travel by public transport (most of these results are reported in Naess 2009;Naess 2010;and Pinho & Silva 2015). The demonstration of a separate and considerable effect on travel behavior from the location of the dwelling relative to the city center, also when controlling for socio-demographics and residential self-selection, is in line with the findings by Hammond (2005), Bhat & Guo (2007), Zhou & Kockelman (2008), Chatman (2009), Cao (2010, and Cao et al (2010).…”
Section: A) the Causal Mechanisms By Which Residential Location Influmentioning
confidence: 92%
“…Besides presenting theoretical arguments, the paper will draw on empirical studies conducted by myself and colleagues in different cities, especially the studies in Copenhagen Metropolitan Area, Denmark (Naess 2005(Naess , 2006a(Naess and b, 2009, Hangzhou Metropolitan Area, China (Naess 2010 and) and a still on-going study in Greater Oporto, Portugal (Pinho & Silva 2015). All these studies have been carried out by means of a combination of qualitative and quantitative research methods.…”
Section: Introductionmentioning
confidence: 99%
“…To what extent can the observed association between built environment and activity and travel behavior reported in the previous studies be attributed to residential self-selection? To the knowledge of the authors, there is hardly any travel behavior study of urban China that explicitly addresses the issue of residential self-selection except Naess (2010), which examines the residential location and travel behavior in Hangzhou, China, and suggests that the observed geographical differences in travel behavior cannot be explained by residential self-selection.…”
mentioning
confidence: 99%